Government benefits, inequality, and employment - Lane Kenworthy (Luxembourg Income Study (LIS), 2008)
Redistribution is one of the principal mechanisms through which countries secure low income inequality. Maintaining moderately high wage levels at the low end of the distribution may be increasingly difficult and perhaps even counterproductive from an egalitarian perspective. If so, redistribution is likely to become even more critical. Redistribution can be achieved through the tax system, via government transfers, or both. In practice, however, very little redistribution is accomplished via taxation, and a shift toward greater use of taxes to achieve redistributive ends is unlikely. Benefits, therefore, may be the key to successful pursuit of low inequality for affluent countries. But generous benefits can create employment disincentives. This produces a bind for policy makers. Generous benefits secure the redistribution countries need to get low inequality. Because of aging and capital mobility, a high employment rate is needed to finance those benefits. But if benefits are generous, they may reduce the employment rate. Is there a way out of this dilemma?
Keywords: 330; Einkommensverteilung; Einkommensumverteilung; Öffentliche Sozialleistungen; Sozialpolitik; Beschäftigungseffekt; OECD-Staaten